2016
DOI: 10.1016/j.bmc.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and investigation of novel benzimidazole derivatives as antifungal agents

Abstract: The rise and emergence of resistance to antifungal drugs by diverse pathogenic fungal strains have resulted in an increase in demand for new antifungal agents. Various heterocyclic scaffolds with different mechanism of action against fungi have been investigated in the past. Herein, we report the synthesis and antifungal activities of 18 alkylated mono-, bis-, and trisbenzimidazole derivatives, their toxicities against mammalian cells, as well as their ability to induce reactive oxygen species (ROS) in yeast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…The results indicate that increasing the length of the alkyl chain on the 1,2,3-triazolium rings results in a decrease in antifungal activity of starch derivatives (P < 0.05) against all the targeted microorganisms and the antifungal activity increases in the order of 2a > 2b > 2c > 2d > 1a ∼ 1d > starch. It was in accordance with the conclusions of Chandrika et al (2016), Garudachari, Isloor, Satyanarayana, Fun, and Hegde (2014); Yao et al, 2012; while some studies had shown that an increase in chain length of alkyl substituted groups corresponded with an increase in antifungal activity (Zhao et al, 2016). The reasonable interpretation was that the longer alkyl groups had the stronger electron-donating ability and tended to donate more electrons to 1,2,3-triazolium moieties accordingly, which inevitably caused the decrease in the positive charge density of 1,2,3-triazolium moieties and eventually led to reducing in antifungal property (Guo et al, 2007).…”
Section: Antifungal Activitysupporting
confidence: 79%
See 1 more Smart Citation
“…The results indicate that increasing the length of the alkyl chain on the 1,2,3-triazolium rings results in a decrease in antifungal activity of starch derivatives (P < 0.05) against all the targeted microorganisms and the antifungal activity increases in the order of 2a > 2b > 2c > 2d > 1a ∼ 1d > starch. It was in accordance with the conclusions of Chandrika et al (2016), Garudachari, Isloor, Satyanarayana, Fun, and Hegde (2014); Yao et al, 2012; while some studies had shown that an increase in chain length of alkyl substituted groups corresponded with an increase in antifungal activity (Zhao et al, 2016). The reasonable interpretation was that the longer alkyl groups had the stronger electron-donating ability and tended to donate more electrons to 1,2,3-triazolium moieties accordingly, which inevitably caused the decrease in the positive charge density of 1,2,3-triazolium moieties and eventually led to reducing in antifungal property (Guo et al, 2007).…”
Section: Antifungal Activitysupporting
confidence: 79%
“…Many studies from the past had reported that the length of the alkyl groups was an important determinant of antifungal activity (Chandrika, Shrestha, Ngo, & Garneau-Tsodikova, 2016;Luo et al, 2009). Therefore, the effect of the length of the alkyl groups in 1,2,3-triazolium-functionalized starch derivatives on antifungal activity is also evaluated in this paper.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…This has been followed by the compounds IVc, IVd and IVn with an IC 50 of 10.52, 10.61 and 10.98 M, respectively. In an attempt to synthesize gastro-sparing antiinflammatory agents, Sharma et al [17] has reported antioxidant activity of 5-methanesulphonamido benzimidazole derivatives.…”
Section: Biological Activitymentioning
confidence: 99%
“…Benzimidazoles represent a class of medicinally important multi-faceted amalgams with a diverse range of biological and pharmaceutical activities. [1] They possess antifungal, [2] anticancer, [3] antibacterial, [4] antiviral, [5] anti-HIV, [6] anti-inflammatory, [7] antidepressant [8] and antidiabetic [9] properties. Some of the most commonly used drugs with a benzimidazole core are presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%